The burden of nonrheumatic valvular heart diseases in Iran between 1990 and 2017: Results from the global burden of disease study 2017. (April 2022) - Arabloo, Jalal; Omidi, Negar; Rezapour, Aziz; Sarabi Asiabar, Ali; Mojtaba Ghorashi, Seyyed; Azari, Samad
Abstract: Background: Nonrheumatic valvular heart diseases (NRVDs) are some of the common and treatable cardiovascular diseases. The objective of this study was to describe the burden of NRVDs in Iran from 1990 to 2017 and to compare the findings with those from the world and in particular, the North Africa and Middle East (NAME) region. Methods: Using publicly available estimates from the Global Burden of Disease 2017 Study (the GBD 2017 Study) for Iran and the NAME region, we reported the years of life lost (YLLs), years lived with disability (YLDs), disability-adjusted life years (DALYs), and the prevalence for NRVDs by age group and sex between 1990 and 2017. Results: There were an estimated 174, 071 cases and 957 deaths from NRVDs in Iran in 2017. In addition, 1844 YLDs, 21, 661 YLLs, and 23, 506 DALYs were caused by NRVDs in Iran in 2017. Between 1990 and 2017, the age-standardized prevalence rate increased in Ian by 15%, the death rate by 15.3%, and DALYs by 2%. Nevertheless, in the world and the NAME region, the age-standardized rates for DALYs and deaths decreased and the age-standardized prevalence rate increased till 2017. Conclusions: The burden of NRVDs is on the rise in Iran. A reduction in the burden of NRVDs in Iran requires the development of appropriate plans to meet the health needs of patients, the decrease of the modifiable risk factors, the allocation of adequate resources for the early diagnosis and management of the diseases, and an improvement in access to treatment technologies.